Structure–properties relationships in fibre drawing of bioactive phosphate glasses - Muñoz-Senovilla, Laura; Muñoz, Francisco; Tricot, Gregory; Ahmed, Ifty; Parsons, Andrew J. (Springer, 2017)
New bioactive phosphate glasses suitable for continuous fibre production are investigated in this work. The structure of both bulk and fibres from Na2O–CaO–MgO–P2O5 glasses has been studied by means of Raman and 31P and 23Na nuclear magnetic resonance spectroscopies, and the structural results have been correlated with the mechanical properties of the fibres and the dissolution rate of the bulk glasses. It has been observed that the mechanical properties of the phosphate glass fibres are influenced by the glass network connectivity, while the dissolution rates are governed by the Qi speciation of the PO4 units. As seen in previous studies, molar volume seems to play an important role in the fragility behaviour of phosphate glasses. Here, a lower molar volume resulting from the increase in the oxygen packing density hinders the cooperative flow of the PO4 units throughout the glass network and, therefore, causes a reduction in the kinetic fragility.